Longphuirt, Wintersetlu, and Gorodišče: A Study of Viking Age Scandinavian Sites in Ireland, England, Russia, and Ukraine from the Eighth to the Tenth Centuries - Pidzamecky, William (2023)
This study examines and compares the beginning of the process of Viking Age Scandinavian migration to Eastern and Western Europe from the mid-eighth to mid-tenth centuries. While there have been comparisons of this process within the same geographic area, there have been few studies with detailed discussions which encompass both eastern and western sites. Using an interdisciplinary methodology, the present study brings together original research from different traditions to address a variety of questions related to areas of Scandinavian occupation such as who lived there? What roles did these sites fulfilled? What their impact was on identity? The cross-perspective approach focuses on a selection of case study sites located in present day Ireland, England, Russia, and Ukraine. The evidence from each case study is considered in relation to one another as well as to the wider context of Scandinavian occupation in their specific geographic regions. This study reveals that Scandinavian sites of occupation were multi-functional with varying degrees of capability to meet the military, commercial, and domestic needs of the inhabitants. They had the potential to function as administrative centres and nodal points of cross-cultural contact. The significance of this study is that it not only informs and broadens our understanding of Viking Age migration by viewing it as a global phenomenon, but also bridges the scholarly gap between eastern and western Viking Age scholarship.